PDGFRα-positive mesenchymal stem/stromal cells contribute to autonomous vascular formation through in-body tissue architecture - Satoru Morikawa; Masaki Yoda; Takehito Ouchi; Takazumi Yasui; Kazumasa Fukuda; Michiru Sugimoto; Rintaro Harada; Tatsuaki Matsumoto; Yo Mabuchi; Osahiko Tsuji; Narihito Nagoshi; Yoshitaka Kase; et al. (PLoS ONE, 2026)
Driven by endogenous platelet-derived growth factor receptor α (PDGFRα)-positive cells, in-body tissue architecture (iBTA) enables the autonomous formation of vascularized tissues within subcutaneously implanted molds, overcoming the limitations of traditional cell therapies. The cellular mechanisms were investigated in PDGFRα reporter mice. Recruited PDGFRα-lineage cells were closely associated with Pecam-1-positive vessels and often adopted perivascular positions. Flow cytometry revealed that these cells expressed the mesenchymal stem/stromal cell (MSC) markers (CD73, CD90, and CD105). Additionally, the cultured isolates maintained MSC morphology and demonstrated osteogenic, chondrogenic, and adipogenic differentiation potential in vitro. The approach was successfully scaled to a porcine model, which exhibited organized tissue maturation, including vascular structures and collagen deposition, within 2 weeks. iBTA eliminates the need for cell isolation and immunosuppression by leveraging resident PDGFRα-positive MSCs for in situ tissue generation, providing a direct pathway for autologous vascular tissue engineering applications.